Karakteristik Fisikokimia Dan Organoleptik sosis Analog Berbasis Ikan Gabus (Channa striata) Dan Tepung Beras Ketan Hitam (Oryza Sativa Glutinosa) - Clarita Gobel; Muh Tahir; Siti Aisah Liputo (Jambura Journal of Food Technology, 2022)
Snakehead fish is known to contain high protein, especially albumin and black glutinous rice flour which functions as a binder containing antioxidants, so it is good to be developed into processed products such as sausages. This study aims to determine the physicochemical characteristics and acceptability of panelists to analog sausages based on snakehead fish and black glutinous rice flour. The data were analyzed by statistical analysis of variance (ANOVA) at the level of = 5% using the SPSS (Statistical Product and Service Solutions) type 16.0 program, if there was a significant difference between treatments, then continued with Duncan's Multiple Range Test (DMRT). The results showed that from the four analogue sausage treatments of snakehead fish and black glutinous rice flour, the best preferred treatment was the A4 treatment which the results included water content of 59.91%, protein content of 12.04%, fat content of 6.17%, ash content 0.62%, carbohydrates 21.27%, and antioxidant activity 13.84% as well as the organoleptic test for color 5.07%, aroma 5.00%, texture 6.07%, and taste 5.27%.